An Analysis of Flouting of Maxims of Quality in the “Uptown Girls” Movie Used by the Main Character - Marianus Indra Wayon; Ni Wayan Suastini (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2025)
The study, entitled